Adolescents' perceptions of alcohol. Issue 3 (3rd April 2017) - Roy, Amit; Ikonen, Risto; Keinonen, Tuula; Kumar, Kuldeep
Abstract : Purpose: Rising trends in alcohol consumption and early drinking initiation pose serious health risks especially for adolescents. Learner's prior knowledge about alcohol gained from the social surroundings and the media are important sources that can impact the learning outcomes in health education. The purpose of this paper is to map adolescents' perceptions of alcohol in Punjab, India and how these perceptions are related to their attitudes towards their social surroundings and the media. Design/methodology/approach: The questionnaire was created after informal discussions with local people who consume alcohol and discussions with alcohol-related experts. Students from five schools ( n =379, average age=13.6 years) in the urban region of Punjab, India, filled in a questionnaire. Quantitative tests were performed on the questionnaire data. Summative content analysis was performed for the textbook content about alcohol from classes 1 to 10. Findings: Data suggest that students gain knowledge about alcohol from multiple sources, including society, the media and education. While society and the media can give misinformation, education did not provide them with factual scientific information about alcohol. Students from financially marginalized social surroundings experience the presence and use of alcohol more frequently; they trust the media and celebrities somewhat unquestioningly and, hence, are more at-risk. Research limitations/implications: All participants in informal discussions as well as all participating schools in the study were from urban regions. Data about individual's socio-economic conditions was not collected. Originality/value: This research investigates perceptions of alcohol that are derived from adolescents' social surroundings, perceptions of the media and perceptions gained through educational guidance in a developing country. Such multi-dimensional investigations have not been conducted earlier.